Menciptakan Lingkungan Kerja yang Positif Melalui Manajemen Konflik yang Tepat - Achmad Zakaria; Zahra Khoirun Nisa; Moch. Yusrizal Lifanto; Muallimin Muallimin (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Creating a positive work environment through effective conflict management plays a crucial and important role in fostering a productive and harmonious workplace. It was found that conflict resolution techniques such as mediation, negotiation, and a collaborative approach can reduce tension and strengthen relationships among employees. Open communication also proves to be a key factor in managing conflicts constructively, with companies that have transparent communication policies being more capable of creating a harmonious work atmosphere. A proactive approach by managers in handling potential conflicts, as well as ongoing training in conflict resolution, also plays a significant role in creating a healthy and productive environment.